Cybersecurity model for smart city in Indonesia based on actor-network theory - Alam, RG Guntur (2023)
The development of information and communication technology has spread throughout the world, including Indonesia. There are many benefits, but the risks cannot be avoided. Communication is growing massively in cyberspace and thus poses a security threat to smart city services. In Indonesia, cybersecurity has not become a priority and is even considered unimportant. Telecommunications equipment and public service application systems do not yet have sufficient security standards. Policies that regulate all aspects as a standard reference for implementing cybersecurity in smart cities are still needed. Therefore, the purpose of this study is to propose a cybersecurity model in smart cities in Indonesia. In this study, unstructured interviews were conducted as a method for collecting the data. Seven respondents, namely the Director, Head of Cyber and Code Control Section, Head of Operations, and four staff in the Jakarta smart city were chosen as respondents. The initial factors for implementing cybersecurity in Indonesia were identified and analysed qualitatively. Actor-Network Theory (ANT) is used as a theoretical framework to explore the practices of actors involved in implementing cybersecurity in JSC. Moment of translation ANT identified and recommended factors related to cybersecurity. Adapting the Governance Risk and Compliance Model by Jirasek, the identified factors are embedded. In the end, a bureaucracy-based cybersecurity model for smart cities was proposed.The proposed model focuses on people, technology, and process and follows the flow of the government bureaucracy in Indonesia. The bureaucracy-based cybersecurity model for smart cities has three main parts, namely: (1) Cyber Security Stakeholders, (2) Legal Fundamentals of Cyber Security Management, and (3) Security Management. The contributions of this research include (1) critical success factors to guide the development of smart cities with cybersecurity elements, (2) a cybersecurity development model for the government agencies to design and implement cybersecurity in Smart city projects in Indonesia, and (3) evidence that ANT as a useful analytical tool to understand the interaction of social systems and technology, especially related to cybersecurity.